Sub-project 3: fish trade, processing and marketing (Denmark, 1997)
The main report is a summary and an overview of the work carried out and the result reached by Sub-project 3. In accordance with the terms of reference the output of the work of the sub-project is,...
Keywords: Fishery management,Aquaculture; Economic aspects